Characterization of bipolar plates manufactured with various Pb/C ratios for unitized regenerative fuel cell system - Jo, Chanmin; Lim, Yoongu; Moon, Dae Jun; Yoo, Seungryul; Seok, Dong Chan; Jung, Seon Yeop; Jung, Seunghun; Jung, Ho-Young; Sim, Uk (Frontiers in Chemistry, 2023)
The weight reduction of the bipolar plate (BP) is distinctly essential for the commercialization of unitized regenerative fuel cells (URFCs). In order to lighten the weight of the bipolar plate, we have used Pb/C composite powder as a cost-effective primary material, which is a mixture of low-density graphite and lead. Further, varied lead-carbon weight ratios (1: 8, 1:4, 1:1, 4:1, and 8:1) were investigated for fabricating the bipolar plate by hot-pressing process adding styrene-butadiene rubber (SBR) as a binder. The specific surface area, porosity, and microstructure characteristics corresponding to the varied lead-graphite ratio of the prepared bipolar plates were studied. The relative difference in conductivity upon the compressibility of the plates is also examined. Finally, the wettability and electrochemical properties of the prepared bipolar plates were evaluated through water contact angle and cyclic voltammetry analysis.